Seabird mortality induced by land-based artificial lights - Rodríguez, Airam; Holmes, Nick D.; Ryan, Peter G.; Wilson, Kerry-Jayne; Faulquier, Lucie; Murillo, Yovana; Raine, André F.; Penniman, Jay F.; Neves, Verónica; Rodríguez, Beneharo; Negro, Juan J.; Chiaradia, André; et al. (Conservation biology, 2017)
Artificial lights at night cause high mortality of seabirds, one of the most endangered groups of birds globally. Fledglings of burrow-nesting seabirds, and to a lesser extent adults, are attracted to and then grounded (i.e., forced to land) by lights when they fly at night. We reviewed the current state of knowledge of seabird attraction to light to identify information gaps and propose measures to address the problem. Although species in families such as Alcidae and Anatidae can be grounded by artificial light, the most affected seabirds are petrels and shearwaters (Procellariiformes). At least 56 species of Procellariiformes, more than one-third of them (24) threatened, are subject to grounding by lights. Seabirds grounded by lights have been found worldwide, mainly on oceanic islands but also at some continental locations. Petrel breeding grounds confined to formerly uninhabited islands are particularly at risk from light pollution due to tourism and urban sprawl. Where it is impractical to ban external lights, rescue programs of grounded birds offer the most immediate and employed mitigation to reduce the rate of light-induced mortality and save thousands of birds every year. These programs also provide useful information for seabird management. However, these data are typically fragmentary, biased, and uncertain and can lead to inaccurate impact estimates and poor understanding of the phenomenon of seabird attraction to lights. We believe the most urgently needed actions to mitigate and understand light-induced mortality of seabirds are estimation of mortality and effects on populations; determination of threshold light levels and safe distances from light sources; documentation of the fate of rescued birds; improvement of rescue campaigns, particularly in terms of increasing recovery rates and level of care; and research on seabird-friendly lights to reduce attraction. Las luces artificiales nocturnas causan una mortalidad alta de aves marinas, uno de los grupos de aves en mayor peligro de extinción a nivel mundial Lospolluelos de aves marinas que anidan en madrigueras, y en menor medida los adultos, son atraídos y forzados a aterrizar por las luces cuando vuelan de noche. Revisamos el estado actual del conocimiento sobre la atracción de las aves marinas por la luz para identificar vacíos de información y proponer medidas para resolver el problema. Aunque las especies de familias como Alcidae y Anatidae pueden ser forzadas a aterrizar por la luz artificial, las aves marinas más afectadas son los petreles y las pardelas (Procellariiformes). Por lo menos 56 especies de Procellariiformes, más de un tercio (24) de ellas amenazadas, son propensas al aterrizaje atraídas por las luces. Las aves marinas forzadas a aterrizar han sido halladas en todo el mundo, principalmente en islas oceánicas, pero también en algunas localidades continentales. Los sitios de anidación de los petreles confinados anteriormente a islas deshabitadas están particularmente en riesgo de sufrir contaminación lumínica debido al turismo y al crecimiento urbano. En donde no es práctico prohibir las luces externas, los programas de rescate de las aves accidentadas ofrecen la mitigación más inmediata y empleada para reducir la tasa de mortalidad inducida por la luz y salvar a miles de aves cada año. Estos programas también proporcionan información útil para el manejo de aves marinas. Sin embargo, estos datos están típicamente fragmentados, sesgados y son inciertos, y pueden llevar a estimaciones inexactas del impacto y a un entendimiento pobre del fenómeno de la atracción de las aves marinas por la luz. Creemos que las acciones necesarias de mayor urgencia para mitigar y entender la mortalidad de aves marinas producida por la luz son: la estimación de la mortalidad y los efectos sobre la población; la determinación de umbrales de niveles de luz y de distancias seguras a las fuentes de luz; el estudio del destino de las aves rescatadas; la mejora de las campañas de rescate, particularmente en términos de incrementar las tasas de recogida y el nivel de cuidado; y la investigación sobre las características de la luz para reducir la atracción de las aves marinas.